Rancangan Pengembangan Jasa Rumah Makan dengan Menggunakan Metode QFD (Studi Kasus: Rumah Makan Seteran Semarang, Bandung) - Andreas, Michael; Wawolumaja, Rudy (Zenit, 2014)
This applied research is done at Seteran Semarang Restaurant in Bandung as a business development model by opening a new branch at Paskal Hyper Square Bandung. The variables used for the service qualities of what consumers want are variables derived from 5 main dimensions according to Parasuraman V. A Zeithaml and L.L Berry. Those five main dimensions are tangibles, reliability, responsiveness, assurance, and empathy. The result of QFD part 1 shows that there are 35consumer needs, which are arranged according to priority scale as proposed by the previous 5 main dimensions and there are 43 technical efforts needed to meet these consumer needs. The 43 technical efforts require 47 design characteristics which are shown in QFD part 2 and to be further deployed to part 3. The third part of QFD produces 68 characterictics of process which must be done in order to fulfill the 47 design characterictics in the second part. The goal of this research is to design servicedevelopment model by deploying from consumer needs into the process characteristics according to the priority scale.Keywords: QFD ( Quality Function Development ), Service Quality.